Faktor-Faktor yang memengaruhi Kepatuhan Wajib Pajak dalam Membayar Pajak Kendaraan Bermotor di Jakarta Barat - Dhea Cellynia; Aan Marlinah (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study aims to determine the effect of awareness of taxpayer, tax sanctions, service quality, tax knowledge, and compliance costs towards taxpayer compliance. The methodology used in this research is primary quantitative with sampling technique using the convenience sampling method. The number of samples used in this study were 102 respondents with sample research criteria, namely taxpayers who were registered in the West Jakarta area, made their own payments, had made payments to the SAMSAT Office in the West Jakarta area, and had received tax services by tax officials. The results of data analysis show that tax sanctions and tax knowledge has a positive effect on taxpayer compliance and awareness of taxpayer, service quality, tax socialization, and compliance costs have no effect on taxpayer compliance.